Poultry vaccines: an innovation for food safety and security - Bejo, Mohd Hair (Universiti Putra Malaysia Press, 2010)

(untitled)
The poultry industry in Malaysia has played its role in contributing to the realization of agriculture as the third engine of growth and a high income economy, which is the goal of the new economic model (NEM) and food security. The industry has grown significantly at about 5.95% annually from 714,300 to 1.202 million metric tonnes from year 2000 to 2009, with total ex-farm value of RM5.468 billion or 53% of ex-farm value of the livestock industry. The total export of chicken products increased from RM54.44 million in 2007 to RM 350.68 million in 2009. In addition, 510 million metric tonnes of eggs was produced in 2009, with total ex-farm value of RM2.226 billion or 22% of ex-farm value of the livestock industry. The industry has contributed 86% of livestock production and 75% of the ex-farm value of the livestock industry in the country. Poultry products are a major source of protein which is relatively cheap, easily available and acceptable to most or a majority of the society in the country and worldwide: we feed the world. The industry is run commercially by large-scale integrators and multi-national corporations and is an example of a success story in the livestock industry in the country, and could perhaps act as model for the livestock industry. However, the industry is not free from many issues and challenges such as high production costs and emerging and reemerging diseases. To date, almost all known major poultry diseases have been reported in Malaysia. Thus, without proper management programmes and appropriate intervention the health and production of chickens, as well as the quality and safety of the products, can be badly affected. The success of chicken production depends to a significant degree on the flock health and prevention of diseases. Most problems related to disease in the chicken industry today are caused by the interaction of many factors where immunosuppression plays a key role and is a frequent problem in chicken production. Control and prevention of poultry diseases involves complex understanding of the interaction of the agent, host and environment, and this can usually be achieved by proper biosecurity, vaccination and flock health programmes. It is difficult and expensive to maintain a high level of biosecurity at all times. Thus, poultry vaccines are powerful tools in disease control and prevention. Malaysia imports vaccines and pharmaceuticals worth RM 650 million annually and thus the Department of Veterinary Service is looking into ways of producing at least 30% of these vaccines locally. While there are 35 veterinary vaccine importers in Malaysia, Malaysian Vaccines and Pharmaceuticals Sdn Bhd (MVP) is currently the sole veterinary vaccines manufacturer in the country. MVP manufactures 10 poultry vaccines against 4 important poultry diseases, namely the NDV4, FP, IBD UPM93, IBD, NDF, NDS, NDB1, NDLasota, NDB1/H120 and NDLa/H120. Of these, 3 of the vaccines against 3 important poultry diseases, namely the NDV4, FP and IBD UPM93, are innovations from our research team at the Faculty of Veterinary Medicine, Universiti Putra Malaysia. The vaccines manufactured by MVP are for the local and export markets in ASEAN, Asia and West African countries. Recently, MVP Life Sciences Sdn Bhd, the second vaccine company in Malaysia, was established to focus on the manufacturing of tissue culture based-vaccines and a new generation of vaccines using bioreactors and latest technology in vaccine production. Innovation to produce safe and effective poultry vaccines, which are also cheap, efficient and better, is the priority in local vaccine production. This can be achieved through advanced knowledge in animal biotechnology and molecular biology. It appears that conventional type vaccines will still be the main type of vaccine produced in the near future, but new generation vaccines hold the promise of more advantages although there is a big horizon to explore before thisbecomes a reality